Pedampingan Proses Pembuatan Usaha Krupuk Nasi di Desa Sidoharjo Kecamatan Pulung - Eko Setyowan; Medina Nur Asyifa Purnama (Institut Agama Islam Sunan Giri Ponorogo, 2023)
interesting, because you are so aware of the many figures for the value of income from the rice cracker business. Assistance in the process of making crackers aims to benefit farmers in the Sidoharjo village community, because in that village there are many incomes that can be produced, it seems that one of them is rice plants, rice can be made into rice crackers. The objects or targets in this assistance are men and women from the high school level up to ladies and gentlemen. The method used is Asset Based Community Development (ABCD). In carrying out the assistance in the manufacturing process, namely with a learning assistance model that is carried out for 1 month, and also by practicing. The material provided include: Instructions/steps of manufacture/processing Process the size of seasoning compounding Manufacturing process. Packaging process. The cooking process Cooling process. Cutting process The drying process The results of this assistance are to increase the results of farmer's efforts so that farmers get higher profits than the previous profits It has been seen that there are efforts to develop and improve their skills in making these crackers